Pituitary Metastatic Composite Tumors: A Case Report with Next-Generation Sequencing and Review of the Literature. (21st July 2020) - Helton, Matthew; Abu-Rmaileh, Muhammad; Thomas, Kevin; Gokden, Murat; Kanaan, Alissa; Rodriguez, Analiz
Abstract : Background . While pituitary tumors are well understood, little research has been done on metastasis from primary tumors into pituitary adenomas, also known as composite tumors. Because only 34 cases of composite tumors have been reported to date, we hope to better characterize these tumors by reviewing cases reported in the literature and reviewed our own documented case, which includes next-generation sequencing. Case Presentation . A 74-year-old man presented to the emergency department with left vision loss for 3 months. He had a history of colon cancer treated with colectomy and clear cell renal carcinoma treated with left nephrectomy. A preoperative MRI demonstrated growth of a peripherally enhancing, centrally necrotic mass with sellar expansion measuring 5.7 × 3.1 × 3.0   cm . Given these findings, an endoscopic endonasal transsphenoidal resection was performed. Histological assessment revealed a composite tumor: one neoplasm was a nonfunctioning pituitary adenoma, and another neoplasm was a clear cell carcinoma. Next-generation sequencing demonstrated that the tumors shared mutations in VHL and Notch 2. The patient died 2 months later from systemic metastatic cancer. Conclusion . From our literature review, most metastatic lesions in these composite tumors originated from neoplasms of the lung and kidney. Approximately 63% patients presented with ophthalmoplegia as the initial symptom while 23% displayed hormonal abnormalities. Postoperative mortality had a median of 3.5 months. In our patient, the presence of VHL and Notch 2 mutations in both tumors highlights the possibility of using next-generation sequencing to help identify therapeutic targets even in complex composite neoplasms.